TP53 and PTEN mutations were shared in concurrent germ cell tumor and acute megakaryoblastic leukemia - Akizuki, Keiichi (BMC Cancer, 2020)
BACKGROUND: The occurrence of a mediastinal germ cell tumor (GCT) and hematological malignancy in the same patient is very rare. Due to its rarity, there have been only two reports of the concurrent cases undergoing detailed genetic analysis with whole-exome sequencing (WES), and the possible clonal relationship between the both tumors remained not fully elucidated. METHODS: We performed whole-exome sequencing analysis of mediastinal GCT and acute myeloid leukemia (AML) samples obtained from one young Japanese male adult patient with concurrent both tumors, and investigated the possible clonal relationship between them. RESULTS: Sixteen somatic mutations were detected in the mediastinal GCT sample and 18 somatic mutations in the AML sample. Mutations in nine genes, including TP53 and PTEN both known as tumor suppressor genes, were shared in both tumors. CONCLUSIONS: All in our case and in the previous two cases with concurrent mediastinal GCT and AML undergoing with whole-exome sequencing analysis, TP53 and PTEN mutations were commonly shared in both tumors. These data not only suggest that these tumors share a common founding clone, but also indicate that associated mediastinal GCT and AML harboring TP53 and PTEN mutations represent a unique biological entity.